(untitled) (Journal of Pharmaceutical Negative Results, 2023)
(1) Purpose: to determine the shear bond strength (SBS) of a repair composite to a monolithic zirconia veneer (5Y) after applying various resin bonding materials and pretreatments to the zirconia surface. (2) Methods: A total of 54 zirconia discs (1.7 × 7 mm × 7 mm) were manufactured and classified into three primary groups based on their surface treatments: control (A), sandblasting with 50 µm Al2O3 particles at a distance of 10 mm under 4 atm (B), and stone bur roughening (C). Each of the three main groups was subdivided into three subgroups based on the adhesive material applied following surface treatment. All samples were evaluated for SBS following cementation, following resin-composite repair and before shear bond strength testing (SBS). All hydrothermal aging of the specimens was carried out in an autoclave set to 134 c. The resin-substrate contact was loaded at a shear rate of one millimeter per minute. Three-way ANOVA and Tukey’s tests were used to assess the data (MPa) (p ≤ 0.05) (3) The SBS values of the surface-treated samples were statistically different (p ≤ 0.001) regardless of the adhesive type. There was a statistically significant difference in the SBS values of the surface-treated samples. The highest mean SBS value (15.423.86) was found in Group stone bur, followed by Group B sandblasting (9.431.92) and Group A no surface test (7.011.02). Resin bond samples recorded the highest mean values regardless of the type of surface treatment and the values had a statistically significant difference (p 0.001). The resin bond recorded the highest values (16.14 3.43), followed by adhesive cement samples (8.71 ± 3.35), and finally, the zircon primer samples (7.11 5.56). The paired differences by t_test paired samples reported a significant statistical difference between resin bond samples and the other two adhesive samples (p 0.000) (4) Conclusions: The roughness of the stone bur and the resin bond samples increased the shear bond strength of the repair composite resin to zirconia. When monolithic zirconia restorations fail, sandblasting with resin bond or adhesive resin cement may be better than zirconia primer.